2010
DOI: 10.1242/jeb.042820
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine enhances memory of operantly conditioned respiratory behavior in the snail Lymnaea stagnalis

Abstract: SUMMARYAmphetamines have been used as cognitive enhancers to promote learning and memory. Amphetamines are also drugs of abuse that may promote the initiation of strong memories that ultimately lead to addiction. To understand how methamphetamine (Meth) may be augmenting learning and memory, we chose a relatively simple system, the pond snail, Lymnaea stagnalis. We studied the effects of Meth exposure on the long-term memory (LTM), extinction and reinstatement of operantly conditioned aerial respiratory behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…Additionally, yoked control snails trained in epi-PW do not exhibit LTM; therefore, the decrease in breathing attempts in trained snails was not due to prolonged effects of drug exposure or a generalised sensitization to a physical stimulus. Enhancement of LTM following exposure to methamphetamine has also been shown to occur at a concentration that did not alter homeostatic aerial respiratory behaviour (Kennedy et al, 2010). Thus, we strongly conclude that epi directly affects the activity of neurons that are necessary for LTM formation.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Additionally, yoked control snails trained in epi-PW do not exhibit LTM; therefore, the decrease in breathing attempts in trained snails was not due to prolonged effects of drug exposure or a generalised sensitization to a physical stimulus. Enhancement of LTM following exposure to methamphetamine has also been shown to occur at a concentration that did not alter homeostatic aerial respiratory behaviour (Kennedy et al, 2010). Thus, we strongly conclude that epi directly affects the activity of neurons that are necessary for LTM formation.…”
Section: Discussionsupporting
confidence: 52%
“…We have previously demonstrated extinction in Lymnaea (McComb et al, 2002), and we further demonstrated that extinction can be extended or enhanced by a number of different means, including blocking newer memory formation (Sangha et al, 2003e;Sangha et al, 2005;Knezevic et al, 2011). Additionally, animals that have apparently forgotten exhibit re-instatement of the original training following a protocol that does not typically result in LTM formation (Sangha et al, 2003b;Carter et al, 2006;Parvez et al, 2006;Kennedy et al, 2010). We chose to assess the effects of (-)epicatechin (epi), as it has been identified as a bioactive molecule in vivo (Schroeter et al, 2006) and is also commonly consumed through cocoa, green tea, blueberries and red wine (Spencer, 2008).…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…Fig. 2 Our previous study demonstrated that pre-exposure to Meth 24 h prior to training enhanced the ability to form 24 h LTM after a single training session (Kennedy et al, 2010). We conducted additional pilot studies (not shown) to assess the time interval during which Meth pre-exposure produced maximal effects on memory persistence, which was 4 h. Fig.…”
Section: Introductionmentioning
confidence: 89%
“…First, we tested the impact of 5-HT because of previous work describing enhanced memory in Aplysia via changes in DNA methylation status (Rajasethupathy et al, 2012). Second, we previously reported that the psychostimulant drugs cocaine (Carter et al, 2006) and Meth (Kennedy et al, 2010) enhanced long-term memory (LTM) in snails. We also demonstrated that pre-exposure to Meth prior to weak training produced LTM of respiratory behavior that was not found in controls.…”
Section: Introductionmentioning
confidence: 99%